Cartilage macromolecules in knee joint synovial fluid. Markers of the disease course in patients with acute oligoarthritis. Issue 12 (1st December 1997) - Lindqvist, Elisabet; Saxne, Tore
Abstract : OBJECTIVE: To investigate the development of chronic joint symptoms in patients presenting with acute oligoarthritis including knee joint synovitis with effusion and explore whether prognostic information can be derived from initial synovial fluid concentrations of aggrecan and cartilage oligomeric matrix protein (COMP) for development of chronic joint symptoms. METHODS: Retrospective follow up of 25 patients identified in a bank of knee joint synovial fluids collected consecutively from patients presenting with knee joint synovitis and symptoms from at most three additional joints and in whom no diagnosis could be established at presentation. RESULTS: The 10 patients who developed chronic joint symptoms were characterised by lower knee joint synovial fluid concentrations of aggrecan as well as lower aggrecan/COMP ratios (p<0.001) than the 15 patients who had a transient arthritis. No other clinical or laboratory differences between the groups were apparent at the time of presentation. CONCLUSIONS: The synovial fluid content of aggrecan is a potential tool in acute arthritis for distinguishing patients with a benign disease course from those who will develop a chronic joint disorder.